A conceptual framework for the development of iridium(iii) complex-based electrogenerated chemiluminescence labels. Issue 37 (9th August 2019) - Chen, Lifen; Hayne, David J.; Doeven, Egan H.; Agugiaro, Johnny; Wilson, David J. D.; Henderson, Luke C.; Connell, Timothy U.; Nai, Yi Heng; Alexander, Richard; Carrara, Serena; Hogan, Conor F.; Donnelly, Paul S.; et al.
Abstract : A new strategy to create iridium(iii )-based ECL labels reveals limitations of conventional approaches. Abstract : Translation of the highly promising electrogenerated chemiluminescence (ECL) properties of Ir(iii ) complexes (with tri- n -propylamine (TPrA) as a co-reactant) into a new generation of ECL labels for ligand binding assays necessitates the introduction of functionality suitable for bioconjugation. Modification of the ligands, however, can affect not only the photophysical and electrochemical properties of the complex, but also the reaction pathways available to generate light. Through a combined theoretical and experimental study, we reveal the limitations of conventional approaches to the design of electrochemiluminophores and introduce a new class of ECL label, [Ir(C^N)2 (pt-TOxT-Sq)] + (where C^N is a range of possible cyclometalating ligands, and pt-TOxT-Sq is a pyridyltriazole ligand with trioxatridecane chain and squarate amide ethyl ester), which outperformed commercial Ir(iii ) complex labels in two commonly used assay formats. Predicted limits on the redox potentials and emission wavelengths of Ir(iii ) complexes capable of generating ECL via the dominant pathway applicable in microbead supported ECL assays were experimentally verified by measuring the ECL intensities of the parent luminophores at different applied potentials, and comparing the ECL responses for the corresponding labels under assay conditions. This study provides a framework to tailor ECL labels for specific assay conditions and a fundamental understanding of the ECL pathways that will underpin exploration of new luminophores and co-reactants.